Specific inhibition of the Survivin–CRM1 interaction by peptide-modified molecular tweezers - Annika Meiners (Nature Portfolio, 2021)
Survivin’s dual function as apoptosis inhibitor and regulator of cell proliferation is mediated via its interaction with the export receptor CRM1. Here authors report a strategy addressing its dimer interface overlapping with the nuclear export signal, the binding site of CRM1, with advanced supramolecular tweezers for lysine and arginine.